Confident pluralism : surviving and thriving through deep difference - Inazu, John D. (Chicago : The University of Chicago Press, 2017)
In recent years, the United States has become increasingly polarised and divided. This fissure is evident across the nation in conflict over LGBTQ rights; in challenges to religious liberty; in clashes over abortion; in tensions between law enforcement and minority communities. With all of this physical and emotional violence enacted by the legal system and such seemingly irresolvable differences in beliefs, values, and identities across the country, we are forced to ask - how can the people of the nation ever live in peace together? John D. Inazu analyses the current state of the country, orients the contemporary United States within its broader history, and explores the ways that Americans can - and must - live together peaceably despite these deeply engrained differences.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 15, 2016).
Keywords: Multiculturalism -- United States; Cultural pluralism -- United States; Constitutional law -- Social aspects -- United States; Society; United States of America, USA; Jurisprudence & general issues; Law & society, sociology of law